High residual inflammation despite HIV viral suppression: Lessons learned from real‐time adherence monitoring among people with HIV in Africa. Issue 5 (26th October 2021) - Castillo‐Mancilla, Jose R.; Musinguzi, Nicholas; Asiimwe, Stephen; Siedner, Mark J.; Orrell, Catherine; Bangsberg, David R.; Haberer, Jessica E.
Abstract: Background: Lower antiretroviral therapy (ART) adherence is associated with higher systemic inflammation in virally suppressed people with HIV (PWH); however, previous studies have mostly relied on subjective adherence measures and have not assessed this association by disease stage upon ART initiation. Methods: In the Monitoring Early Treatment Adherence study, adherence was monitored electronically in real time among adult, treatment‐naïve PWH in Uganda and South Africa who initiated tenofovir disoproxil fumarate/emtricitabine/efavirenz during early‐stage (CD4 > 350 cells/µL) or late‐stage (CD4 < 200 cells/µL) disease. Participants who achieved viral suppression (< 400 copies/mL) at 6 months and remained suppressed after 12 months were analysed. The association between average ART adherence and plasma concentrations of interleukin 6 (IL‐6), soluble CD14 (sCD14) and D‐dimer was evaluated using adjusted multivariable linear regression, stratified by disease stage. Results: In all, 488 PWH (61% women, mean age 35 years) were included in the analysis. Median ART adherence overall was 87%. In adjusted models, every 10% increase in average adherence was associated with a 3.0% decrease in IL‐6 [95% confidence interval (CI): −5.9 to −0.01, p = 0.05] at 12 months. This relationship was observed in PWH with both early‐stage (5.9%, 95% CI: −10.1 to −1.6, p = 0.009) and late‐stage disease (3.7%, 95% CI: −7.2 to −0.2, p = 0.039). No significant associations were found with sCD14 or D‐dimer. Conclusions: Objective ART adherence measurement was inversely associated with systemic inflammation in PWH who achieved viral suppression after ART initiation in sub‐Saharan Africa, with a greater association in those with early‐stage HIV. This finding underscores the importance of ART adherence beyond establishing viral suppression.